2015
DOI: 10.1039/c4cp04636f
|View full text |Cite
|
Sign up to set email alerts
|

An ultrafast molecular rotor based ternary complex in a nanocavity: a potential “turn on” fluorescence sensor for the hydrocarbon chain

Abstract: Formation of a ternary complex by an ultrafast molecular rotor (UMR) with a macrocyclic cavitand has been investigated for the sensitive detection of the alkyl chain of a surfactant. A benzothiazole based UMR, Thioflavin-T (ThT), has been used as a fluorescent probe. It is shown that ThT forms a very weak inclusion complex with γ-cyclodextrin (γ-CD) with an association constant of 8.8 M(-1). However, the addition of a small amount of surfactant results in a significant increase in the emission intensity of ThT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 122 publications
0
10
0
Order By: Relevance
“…Many variations of the Benesi–Hildebrand equation have developed since the initially reported equation (eq , below), in which [ G ] is the initial concentration of guest, [ H ] is the initial concentration of host, I is the signal intensity in the presence of guest (reported as absorbance, luminescence, fluorescence, or phosphorescence values), I 0 is the signal intensity in the absence of guest, ε 0 is the molar extinction coefficient, and K is the association constant. Practically, the numerical data represented in this equation is often derived by plotting 1/[Host] on the x axis and 1/Δ I on the y axis. If a linear relationship is obtained, the slope of this line is taken to represent the association constant. While useful, this method is only valid in cases where the concentration of host is much higher than the concentration of the complex and is typically only used for 1:1 host–guest complexes, although other binding stoichiometries have also been reported …”
Section: Underlying Principles Of Chemosensorsmentioning
confidence: 99%
“…Many variations of the Benesi–Hildebrand equation have developed since the initially reported equation (eq , below), in which [ G ] is the initial concentration of guest, [ H ] is the initial concentration of host, I is the signal intensity in the presence of guest (reported as absorbance, luminescence, fluorescence, or phosphorescence values), I 0 is the signal intensity in the absence of guest, ε 0 is the molar extinction coefficient, and K is the association constant. Practically, the numerical data represented in this equation is often derived by plotting 1/[Host] on the x axis and 1/Δ I on the y axis. If a linear relationship is obtained, the slope of this line is taken to represent the association constant. While useful, this method is only valid in cases where the concentration of host is much higher than the concentration of the complex and is typically only used for 1:1 host–guest complexes, although other binding stoichiometries have also been reported …”
Section: Underlying Principles Of Chemosensorsmentioning
confidence: 99%
“…It is to be noted that unlike other fluorescence sensors mentioned earlier fluorescence enhancement of a UMR is purely due to physical confinement and barely depends on its relative orientation with respect to the confined media. In recent years, such a UMR has been used to characterize different complex environments, such as macrocyclic host molecules, cross-linked polymers, , and biomolecules. , Recently, we have shown that one of the benzothiazole-based UMRs is much more efficient in detecting DNA as compared to most commonly used DNA stains . It was further demonstrated that such UMRs can probe small changes in the secondary structure of DNA, which could not be detected by any other techniques including circular dichroism spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the inclusion of ThT by bcyclodextrin cavity leads to a sizeable increase in emission intensity consistent with the molecular rotor picture of ThT (Singh et al, 2011a). While -CD leads to a sizeable complexation with ThT, -CD, owing to its smaller cavity size, fails to form any complex with ThT, (Singh et al, 2011a) and contrastingly, -CD is able to form both 1:1 complex, (Murudkar et al, 2015) and 1:2 complex, (Singh et al, 2015a) where two ThT molecules are included, displaying an excimer like emission for ThT. Interestingly, sulfobutyl ether derivative of -CD (SBE 7 --CD) significantly improves the complexation of ThT, suggesting crucial role of extended hydrophobic cavities in determining the binding strength of ThT with this class of host molecules (Singh et al, 2015c).…”
Section: Thioflavin-t Interaction With Supramolecularmentioning
confidence: 53%
“…Interestingly, sulfobutyl ether derivative of -CD (SBE 7 --CD) significantly improves the complexation of ThT, suggesting crucial role of extended hydrophobic cavities in determining the binding strength of ThT with this class of host molecules (Singh et al, 2015c). The 1:1 complex of -CD with ThT has been projected as a sensor for hydrocarbon chains, where significant emission enhancement is observed for ThT--CD complex in the presence of hydrocarbon chains of surfactant molecules (Murudkar et al, 2015). This emission enhancement has been ascribed to the formation of ternary complex, ThT--CD-hydrocarbon, which provides a rigid packing of the free space in the cyclodextrin cavity, leading to significant restriction to the torsional relaxation of ThT and thus yielding increase in emission intensity (Murudkar et al, 2015).…”
Section: Thioflavin-t Interaction With Supramolecularmentioning
confidence: 99%